Ngữ nghĩa dữ liệu trong cơ sở dữ liệu quan hệ có giá trị null phụ thuộc ngữ cảnh - Hiền, Bùi Thị Thúy (Journal of Computer Science and Cybernetics, 2016)
In this paper, we consider sematics of data in relational databases with context dependent null values by giving a formal definition of model for a relation which contains context dependent nulls. Some illustrative examples of data semantics are also given.